How do you solve #4y^2 - 3(y-4)=4y(y-1)+3y#? Algebra Linear Equations Multi-Step Equations with Like Terms 1 Answer Go Anna · Stefan V. Apr 23, 2018 Answer: When only one variable is there, an equation can be solved by using simplification and #y=6# in this equation. You can verify it also by putting #y=6# on both sides and the results will be same. Explanation: #4y^2-3(y-4)=4y(y-1)+3y# #4y^2 -3y+12=4y^2-4y+3y " " " " [-3 * (-4)=12, 4y * y=4y^2]# or #4y^2-4y^2 -3y +12=-y# #-3y+12=-y# So #12=3y-y# #2y=12# #y=12/2# # y=6# Hope it helps... Related questions How do you solve multi step equations by combining like terms? How do you solve multi step equation #w + w + 12 = 40#? How do you solve #3p + 4p + 37 = 79#? How do you solve for f: #f-1+2f+f-3=-4#? How do you combine like terms? How do you combine like terms for #-7mn-2mn^2-2mn + 8#? How do you combine like terms for #3x^2 + 21x + 5x + 10x^2#? What is a term? How do you solve #3v+5-7v+18=17#? How do you solve for x in #5x + 7x = 72#? See all questions in Multi-Step Equations with Like Terms Impact of this question 344 views around the world You can reuse this answer Creative Commons License